Finite Element Method (FEM) simulation of static and dynamic compression test - Ong, Yong Jie (2019)
This report presents the results of a simulated model study of static and dynamic compression test with respect to experimental results obtained by other final year student on their studies. Finite element analysis Ansys 19.1 will be used to simulate the engineering problem where it will be translated into mathematical model to be analysed by the software. ASTM E9-09 Static uniaxial compression test will be modelled using Aluminium 6061 T6511to investigate the stress and strain of the specimen and the margin of error with respect to the experiment results. In addition, Split Hopkinson Pressure Bar Test will be simulated for dynamic loading in a controlled environment within the software to ensure the least deviation from experimental results. Similarly, the results will be computed, and compared, as well as discussed on the material behaviour and the probable causes.